e-WOM: Buy or No Buy? - Rifky Agasta Ibrahim; Wella Wella (Universitas Multimedia Nusantara, 2020)
Research on the topic of influence on purchasing decisions on Lazada e-commerce has a purpose, including 1) to find out what factors of E-WOM influence purchasing decisions on Lazada e-commerce. 2) to find out how the overall influence of E-WOM factors on purchasing decisions on Lazada e-commerce. 3) what is the magnitude of the force of these E-WOM factors on purchasing decisions on Lazada e-commerce. The first research result shows that three E-WOM factors influence purchasing decisions on Lazada, namely the characteristics of the review, the features of the reviewers, and the characteristics of the website. The second research result shows that there is an overall influence of E-WOM factors on purchasing decisions on Lazada e-commerce. The results of the third study showed the magnitude of the E-WOM factors was large enough to influence purchasing decisions at 54%. Based on the three results of the study, it can be concluded that consumers currently entrust E-WOM as a trusted marketing communication and will continue to be used in obtaining information about products on e-commerce Lazada.